PENYULUHAN HUKUM TENTANG PEMBUATAN AKTA OLEH NOTARIS - Komang Octaviani Dewi (UNIB Press, 2019)
Research on Legal Counseling concerning the Making of Deed by a Notary based on the lack of clarity of the purpose of legal counseling which will be given in connection with the making of the deed contained in one of the Notary authorities stipulated in UUJN in Article 15 paragraph (2) letter e. Based on the obscurity of the norm, the formulation of the problem is formulated, namely: (1) What are the authorities possessed by the Notary regulated in the UUJN-P? (2) How is the form of legal counseling conducted by a Notary as its authority related to the making of a deed? The aim is to understand the authority possessed by a Notary that is regulated in the UUJN-P and to study related forms of legal counseling that will be carried out by a Notary in connection with the making of deeds so that they can be useful to the readers. The normative legal research method is the method used in this study with the Statute Approach and the Conceptual Approach. The results of the study show that the authority of a Notary that is regulated in UUJN is the authority that comes from the authority of attribution, and is given the main task of the authority, namely the making of authentic deeds. A notary as a public official is also given special authority and other authority in carrying out his position to be able to take a legal action. In the case of the form of legal counseling carried out by a Notary in connection with the making of a deed, it is an explanation of the terms and procedures for making a deed to the parties facing the Notary so that it can determine legal actions to be used in the process of making an authentic deed. With the existence of legal counseling this can prevent the occurrence of violations of law. Keywords: legal counseling, deed, notary